TIPIKAL SANTRI DALAM MENYIKAPI GEMPURAN TREN KONTEN VIDEO TIKTOK: (Santri SMP Bilingual Terpadu Pesantren Modern al-Amanah Junwangi) - Nurani Ahda (Ulumuna: Jurnal Studi Keilsman, 2022)
This study aims to classify the students of the Al-Amanah Junwangi Modern Islamic Boarding School into several behavioral characteristics in responding to the onslaught of tiktok content trends. The method used in this research is descriptive qualitative. The research subjects are students who live in Islamic boarding schools ranging in age from 14 to 16 years by conducting interviews. This study finds that there are 4 types of typical student groupings in responding to the onslaught of tiktok content trends in the current digital era. These are typical observers, typical imitators, typical modifiers, and typical focus.